Evaluation of the Students Access to the 21st Century General Skills at Tabriz University of Medical Sciences, Iran - Firooz Mahmoodi; Firooz Mahmoodi; Zeinab Fiz olah zadeh (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Attention to the necessary skills in time and place are among the most important issues in the evaluation of the quality of academic education. The present study aimed to evaluate the access of students to the 21st century general skills at Tabriz University of Medical Sciences, Iran. Materials and Methods: This cross-sectional, descriptive study was conducted on 300 medical students, who were selected via simple random sampling. Data were collected using the questionnaire developed by Mahmoodi and Mola, which its validity has been confirmed based on expert opinions, and the reliability has been established at the Cronbach's alpha of 0.90. Results: The general skills of the 21st century in the medical students were at an average level in the cognitive and affective domains considering a theoretical average of 3 (P<0.0001). However, the skill level was observed to be above average and favorable in the sociocultural domain (P<0.0001). Conclusion: According to the results, the access of the students at Tabriz University of Medical Sciences to the high-level cognitive and affective skills of the 21st century was average, which should be taken into account for the optimization of the teaching-learning process and improvement of the curricula.